(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to explore the role of modern management and managerial experience in improving the management of governmental organizations, focusing on the Ministry of Education in Taif. The study adopted a descriptive approach and was applied to a random sample of 52 employees and managers in the Ministry of Education in Taif, using a questionnaire consisting of 4 personal questions and 12 main questions. The study found that employees recognize the importance of applying modern management principles to improve organizational performance. There is significant interest in employing technology and digitalization and adopting sustainability and social responsibility principles. The results also indicated the need to develop human resource management practices, apply total quality management principles, and enhance flexibility and innovation. Employees confirmed the importance of managerial experience in improving organizational performance, as managerial experience is a crucial factor in facing challenges, building strong relationships, creating a motivating work environment, and making effective decisions. The study also showed a generational difference in understanding the importance of modern management, while there was no significant difference in appreciating the importance of managerial experience and evaluating the success of organizational management. The study recommended enhancing the work environment by applying modern management principles, improving support for employees’ professional and personal development, increasing recognition and appreciation of their efforts, organizing more activities and events to enhance interaction, improving communication channels, and providing incentives for employees contributing with innovative ideas.